2018
DOI: 10.3389/fphys.2018.00492
|View full text |Cite
|
Sign up to set email alerts
|

What Makes the Harderian Gland Transcriptome Different From Other Chicken Immune Tissues? A Gene Expression Comparative Analysis

Abstract: The Harderian gland is a sparsely characterized immune tissue known to play an important role in local immunity. The function of the Harderian gland, however, is not clearly defined. Measuring the expression of all genes using RNA-seq enables the identification of genes, pathways, or networks of interest. Our relative RNA-seq expression analysis compared the chicken Harderian gland transcriptome to other important primary and secondary immune tissues including the bursa of Fabricius, thymus, and spleen of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…We found only low levels of transcripts for alpha receptor candidates of various IL-6 family cytokines, leukemia inhibitory factor, oncostatin, and ciliary neurotrophic factor receptors (S-Differentially Expressed Genes). An IL-11 receptor alpha candidate which is expressed in the posthatch bursa (McCarthy et al, 2006; Sun et al, 2015; Liu et al, 2016) and Harderian gland (Deist and Lamont, 2018) is of interest. In mammals and chickens, IL-11 is a stromal-derived cytokine controlling various biological properties of cells including proliferation, differentiation, and cytokine production (Xu et al, 2016; Truong et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We found only low levels of transcripts for alpha receptor candidates of various IL-6 family cytokines, leukemia inhibitory factor, oncostatin, and ciliary neurotrophic factor receptors (S-Differentially Expressed Genes). An IL-11 receptor alpha candidate which is expressed in the posthatch bursa (McCarthy et al, 2006; Sun et al, 2015; Liu et al, 2016) and Harderian gland (Deist and Lamont, 2018) is of interest. In mammals and chickens, IL-11 is a stromal-derived cytokine controlling various biological properties of cells including proliferation, differentiation, and cytokine production (Xu et al, 2016; Truong et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, the present study also found a transcriptional upregulation of IL-4 and/or IL-13 in the bursa and HG of C. perfringens -infected chickens. It is also noteworthy that the HG, an important lymphoid tissue located supraorbital in chickens, is a part of the common mucosal system [ 44 ] and a recent study in chickens showed that HG can downregulate inflammatory responses via expression of microRNAs, such as mir-1764 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Серед значної кількості функцій гардерової залози важливе місце має імунна відповідь (Sakai, 1981;Jahan et al, 2018). Дана залоза у курей включає тканинноспецифічну неімунну функцію, а також унікальну імунну функцію на відміну від інших органів імунного захисту (Deist & Lamont, 2018).…”
Section: вступunclassified